Histogenesis and mode of growth of scrotum in foetal goat - MALIK, M R; TALUJA, J S; PARMAR, M L (The Indian Journal of Animal Sciences, 2013)
Scrotum was measured in 18 goat-foeti of 5.00-35.00 cm CR length. The foetuses were divided into 3 groups on the basis of CR length. Group 1 included the foeti of CR length up to 10 cm; group 2 of 10 + to 20 cm and group:3 of 20cm and above. In foetuses of group 1 the. scrotum was small with thin delicate wall and contained a single cavity. It measured 0.35 these increased to 2,70 cm and 4.55 cm, respectively, in group 3. The position of the scrotum howed a tendency af rostral shift with the advancement of gestation. The single Scrotol cavity (group 1) got panitioned in group 2. The testes descended in the proxiimal half of the scrotion in the specidmen of group 3. All the parameters increased faster (double/triple) in the carly stage of gestalion than late. The thickness of the scrolal wall slarted with a positive but nonsignificant relation with the length and girth of the foctusand acquired negative correlation in the later stages. The hair follicles appeared in the sepcimen of group 2 and oriented radially in the group of 3 in last gestational group. The smooth muscle fibres were inconspicuous inlhe scrotal wall of the foelal goat.